Aracatuba virus: A vaccinialike m virus associated with infection in humans and cattle - Trindade, G. D.; da Fonseca, F. G.; Marques, J. T.; Nogueira, M. L.; Mendes, LCN; Borges, A. S.; Peiro, JR; Pituco, E. M.; Bonjardim, C. A.; Ferreira, PCP; Kroon, E. G. (Center Disease Control, 2003)
We describe a vaccinialike virus, Aragatuba virus, associated with a cowpoxlike outbreak in a dairy herd and a related case of human infection. Diagnosis was based on virus growth characteristics, electron microscopy, and molecular biology techniques. Molecular characterization of the virus was done by using polymerase chain reaction amplification, cloning, an DNA sequencing of conserved orthopoxvirus genes such as the vaccinia growth factor (VGF), thymidine kinase (TK), and hemagglutinin. We used VGF-homologous and TK gene nucleoticle sequences to construct a phylogenetic tree for comparison with other poxviruses. Gene sequences showed 99% homology with vaccinia virus genes and were clustered together with the isolated virus in the phylogenetic tree. Aragatuba virus is very similar to Cantagalo virus, showing the same signature deletion in the gene. Aragatuba virus could be a novel vaccinialike virus or could represent the spread of Cantagalo virus.